The Hotel Syariah di Kota Padang dalam Persepsi Wisatawan Non-Muslim - Mayang Larasati; Berri Brilliant Albar; Junia Mayang Sari (JURISMA : Jurnal Riset Bisnis & Manajemen, 2025)
This study aims to explore non-Muslim tourists' perceptions of Sharia hotels in Padang City, West Sumatra. This research employs a qualitative research design with a case study approach, utilizing primary and secondary data as the main sources. The sampling method used is non-probability sampling, specifically snowball sampling. Data collection was carried out through interviews and literature reviews, with the sample consisting of non-Muslim tourists currently or previously staying in Sharia hotels in Padang. Findings from the field indicate that non-Muslim tourists have generally developed a positive perception of Sharia hotels in Padang. The study also reveals that these perceptions vary, influenced by factors such as the tourists' knowledge and personal experiences during their stay at Sharia hotels in the city. This research is expected to assist Sharia hotel managers in Padang in becoming more responsive to the needs and perceptions of non-Muslim tourists, enabling Sharia hotels to grow as inclusive and competitive accommodation options in the global tourism industry, as they have the same potential for growth as conventional hotels. Keywords: Perception; Non-Muslim Touris; Halal Tourism; Accommodation; Sharia Hotels